(untitled) (Psychology Travelogs, 2023)
The article presents the results of a theoretical analysis and an empirical study of the problem of formation of the motivational component of the attitude to the health of student youth. The analysis of the scientific literature showed that young people are the most promising age category of society in terms of the formation of a healthy lifestyle, therefore the problem of motivation is one of the main ones and is used to indicate the features that determine the attitude to health, stimulate and support behavioral activity at a certain level. Awareness of the importance of health, motivation to preserve and strengthen it contribute to the development of responsibility for self-improvement, self-worth and productive healthy life. The worldview level of the general culture is enriched among the students, the orientation of the individual to support health as a value is formed. Student age is a sensitive period for the formation of life values, motivation and the setting of life tasks, in particular aimed at realizing personal potential and achieving an adequate attitude to health. The study of the peculiarities of the formation of the motivational component of the attitude to health showed that the level of formation of the components of the value attitude to health in the studied students is below average, which is manifested by the location of health as a value not in the leading place of the life values of the individual, a weak awareness of the need to preserve health I and the need to improve health, insufficiently formed motivation for a healthy lifestyle. A comparative analysis of the possible causes of insufficient care for health indicates the overwhelming rejection of responsibility for one’s health, lack of willpower as the main indicator of health carelessness. According to the indicator of the level of motivation to achieve success, an average level of motivation to achieve success is observed - with such motivation, a person is less proactive and persistent in achieving a goal, depends on external incentives, and has a weak orientation to success.